2019
DOI: 10.1111/jfpp.14324
|View full text |Cite
|
Sign up to set email alerts
|

Changes in chicken meat proteins during microwave and electric oven cooking

Abstract: Alterations in proteins and some functional properties of chicken thigh (TM) and breast meats (BM) cooked with microwave oven (MWO) were evaluated in comparison to traditional electric oven (EO). Cooking loss in both TM and BM did not differ between the cooking methods (p > .05). In TM, MWO cooking resulted in higher water‐holding capacity (WHC) than EO (p < .05). Sarcoplasmic protein solubility of TM decreased with MWO cooking while both cooking methods resulted in reduction in both sarcoplasmic and myofibril… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 37 publications
(56 reference statements)
2
19
0
Order By: Relevance
“…Several studies have reported that the performance of microwave heating overpasses that of traditional heating methods. For example, a recent study showed that microwaving chicken thigh and breast meats results in better quality attributes of the cooked products compared to conventional ovens [63]. In another study, microwave cooking was found to improve saltiness perception of grass carp meat, with lower cooking loss and shear force being observed compared to traditional water bath [64].…”
Section: Of 38mentioning
confidence: 99%
“…Several studies have reported that the performance of microwave heating overpasses that of traditional heating methods. For example, a recent study showed that microwaving chicken thigh and breast meats results in better quality attributes of the cooked products compared to conventional ovens [63]. In another study, microwave cooking was found to improve saltiness perception of grass carp meat, with lower cooking loss and shear force being observed compared to traditional water bath [64].…”
Section: Of 38mentioning
confidence: 99%
“…The main obstacles include nonhomogeneous heating and high cost for the equipment, although various solutions have been proposed recently to overcome some of these limitations (Chizoba Ekezie et al 2017). Numerous studies have reported the superiority of microwave heating compared to traditional water bath or oven (Calabrò and Magazù 2012;Han et al 2019b;Li et al 2019;Taşkıran et al 2020). More details about these studies will be given in section 3.…”
Section: Microwave and Radio Frequency Heatingmentioning
confidence: 99%
“…Apart from the sample colour, the results showed an improved texture and better overall flavour of microwave-cooked samples compared to those of conventional boiling cooking. More recently, the microwave cooking was found to be more efficient for cooking thigh and breast chicken meat than a traditional oven (Taşkıran et al 2020).…”
Section: Sensory and Microbiological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Chicken meat is the most commonly consumed meat source in many countries and simultaneously have an increase in consumption and production around the world ( Takran et al., 2020 ). Chicken meat products are available as either sugar-smoked chicken products ( Chen et al., 2013 ) or roast chicken products ( Huang et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%